A theology of the New Testament - Ladd, George Eldon, 1911-1982; Hagner, Donald Alfred (Grand Rapids, MI Eerdmans, 1993)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. -- theology -- textbooks